The Vestibular Implant: Quo Vadis? - Van De Berg, Raymond; Guinand, Nils; GUYOT, Jean-Philippe; Kingma, Herman; Stokroos, Robert (Frontiers in Neurology, 2011)
Abstract Objective: to assess the progress of the development of the vestibular implant and its feasibility short-term. Data sources: a search was performed in Pubmed, Medline and Embase. Key words used were “vestibular prosth*” and “vestibular implant”. The only search limit was language: English or Dutch. Additional sources were medical books, conference lectures and our personal experience with per-operative vestibular stimulation in patients selected for cochlear implantation. Study selection: all studies about the vestibular implant and related topics were included and evaluated by two reviewers. No study was excluded since every study investigated different aspects of the vestibular implant. Data extraction and synthesis: data was extracted by the first author from selected reports, supplemented by additional information, medical books conference lectures. Since each study had its own point of interest with its own outcomes, it was not possible to compare data of different studies. Conclusion: to use a basic vestibular implant in humans seems feasible in the very near future. Investigations show that electric stimulation of the canal nerves induces a nystagmus which corresponds to the plane of the canal which is innervated by the stimulated nerve branch. The brain is able to adapt to a higher baseline stimulation, while still reacting on a dynamic component. The best response will be achieved by a combination of the optimal stimulus (stimulus profile, stimulus location, precompensation), complemented by central vestibular adaptation. The degree of response will probably vary between individuals, depending on pathology and their ability to adapt.